Rethinking interfaith, cultural, ecumenical & religious dialogue in a Nigeria's pluralistic context - Udoekpo, Michael Ufok (Galda Verlag, 2023)
"This erudite compendium "Rethinking Interfaith, Cultural, Ecumenical, and Religious Dialogue in Nigeria's Pluralistic Context," is an edited and expanded proceeding of the Maiden National Conference on Inter-religious Dialogue, held on 12th May, 2022 at Veritas University's (the Catholic University of Nigeria, Abuja) Multi-Purpose Hall; sponsored by John Paul II Center for Inter-religious Dialogue, Rome. Granted that sometimes religions have not only misunderstood other faiths, but eyed them with suspicion and with the tragic distinction that we are the children of light and everyone else the child of darkness, this work represents the contrary. It represents voices from renowned experts of all religious spectrums (Judaism, Christianity, Islam and African Traditional Religions) toward genuine and sincere dialogue, love, justice and peace, respect for one another and unity among world religions." -- Page 4 of cover